The EU institutional reform model and the preferences of the small member states - Veebel, Viljar (Managing global transitions, 2014)
The success of the proposed institutional reform of the EU is of particular importance in the nearest future, as setbacks to reforms may ultimately result in the loss of credibility of the EU as a whole in the international arena. However, the decision whether the existing 'community model' should be renewed or the federal or the stakeholder model should be preferred is rather complicated, as the visions and interests of the member states of the EU widely differ. The article analyses which of these models will be most achievable and most beneficial from the perspective of the small member state of the EU. The research indicated that the renewal of the existing community model seems to be the most rational choice both in terms of measurable quantitative and qualitative aspects from the small EU member state's perspective. The renewal of the existing 'community model' is also most rational choice in terms of applicability.
Keywords: European Union; Evropska unija; federalizacija; stakeholder model; institucionalne reforme; institutional reform; federalization